The Effect of Sales Promotion on Impulse Buying: The Role of Fear of Missing Out (FoMO) as a Moderating Variable in Tokopedia Consumers - Lusi Susilawati; Wala Erpurini (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The fast increase in online shopping in Indonesia has made it harder for e-commerce platforms to stand out from each other. Despite Tokopedia actively holding mega sale campaigns to boost sales, its conversion rate remains low at only 1–1.5%, and its Gross Merchandise Value (GMV) continues to decline while Shopee's visitor numbers and GMV show an upward trend. This condition suggests that impulse buying behavior among Tokopedia users has not been optimally stimulated despite large scale promotions being held. This study looks into haw sales promotion influence impulse buying and checks how fear of missing out (FoMO) affects this relationship among Tokopedia users during big sale events. Through the use of questionnaires given to 104 individuals, data was collected and then analysed using Moderated Regression Analysis (MRA) as a quantitative method. The findings indicate that sales promotions lead to more impulse buying, and feeling anxious about missing out makes this effect even stronger. This means people who experiemce higher levels of FoMO are more likely to make impulse buying when they see promotional offers. These findings imply that promotional strategies designed to generate urgency will be more effective when consumers have high levels of FoMO.